Dietary habits in Australian, New Zealand and Malaysian patients with end stage kidney failure: A pre‐specified cross‐sectional study of the FAVOURED trial participants. Issue 6 (20th January 2022) - Conley, Marguerite; Barden, Anne; Viecelli, Andrea K.; Irish, Ashley B.; Cass, Alan; Hawley, Carmel M.; Voss, David; Pascoe, Elaine M.; Lenhoff, Katie; Polkinghorne, Kevan R.; Hooi, Lai‐Seong; Ong, Loke‐Meng; et al.
Abstract: Background: Dietary management plays an important role in patients with kidney failure. Current dietary habits of Australians and New Zealanders (ANZ) and Malaysians with chronic kidney disease (CKD Stage 4–5) have not been adequately investigated. We report the dietary habits of people with advanced CKD and their adherence to country‐specific dietary guidelines. Methods: Participants with CKD Stage 4–5, enrolled in the Omega‐3 Fatty Acids (Fish oils) and Aspirin in Vascular access Outcomes in Renal Disease (FAVOURED) trial, completed a lifestyle questionnaire at baseline on their dietary intake. Results: Of 567 participants, 538 (ANZ, n = 386; Malaysian, n = 152; mean ± SD age 54.8 ± 14.3 years, 64% male) completed the questionnaire. Dietary fruit and vegetable intakes were higher in ANZ participants; 49% ( n = 189) consumed ≥2 serves day –1 of fruit and 61% ( n = 235) ate ≥2 serves day –1 of vegetables compared to 24% ( n = 36) and 34% ( n = 52) of Malaysians, respectively ( p < 0.0001). Only 4% ( n = 15) of ANZ participants met Australian Dietary recommendations of two fruit and five vegetable serves day –1 . Fish consumption was higher in Malaysians with 83% ( n = 126) consuming ≥2 serves week –1 compared to 21% ( n = 81) of ANZ participants ( p < 0.001). Red meat intake was higher in ANZ participants; however, chicken consumption was similar; 48% ( n = 185) consumed >2 chicken serves week –1 and 65% ( n = 251) ate >2 serves week –1 of red meat compared to 43% ( n = 65) and 15% ( n = 23) of Malaysians, respectively. Conclusions: Significant regional variation in dietary intake for fruit, vegetables and animal protein is described that likely reflects cultural and economic differences. Barriers to meeting recommended dietary intakes require further investigation. Key Points: Dietary management plays an important role in the management of patients with kidney failure. Current dietary habits of Australians, New Zealanders and Malaysians with advanced chronic kidney disease have not been adequately investigated. Dietary fruit and vegetable intakes were significantly higher in Australia and New Zealand (ANZ) participants then Malaysian participants. Fish consumption was higher in Malaysians compared to ANZ participants. The significant regional variation in dietary intake for fruit, vegetables and animal protein likely reflects cultural and economic differences. Dietary intakes of both fruit and vegetables were inadequate by national recommendations but similar to the general population in both the ANZ and Malaysia cohorts. Barriers to meeting recommended dietary intakes require further investigation.